2021
DOI: 10.1002/jbt.22867
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of long noncoding RNA SNHG7 protects against inflammation and apoptosis in Parkinson's disease model by targeting the miR‐425‐5p/TRAF5/NF‐κB axis

Abstract: BackgroundAccumulated evidence has established that long non-coding RNA (lncRNA) is involved in the progress of Parkinson's disease (PD). SNHG7, a novel lncRNA, has been found to play a key role in tumorigenesis.However, the SNHG7 expression and its functional effects on PD remain uncharted. MethodsRT-PCR was used to detect the expression of SNHG7, miR-425-5p and in ammatory cytokines in the plasma of PD patients and the healthy controls. Rotenone (Rot) was adopted to construct PD models in SD rats and SH-SY5Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…SNHG7 is an oncogenic lncRNA on chromosome 9q34.2 and is highly expressed in cancer cells and tumors (Bian et al, 2020 ). Tumor necrosis factor receptor-associated factor 5 (TRAF5) is a cytoplasmic adapter that can trigger the NF-κB signaling pathway via its receptors and can take part in modulating nerve cell death, inflammatory reactions, and other neurological processes (Zhang et al, 2021 ). Zhang et al demonstrated that in PD, SNHG7 works as a ceRNA by sponging miR-425-5p and promoting TRAF5 (Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNHG7 is an oncogenic lncRNA on chromosome 9q34.2 and is highly expressed in cancer cells and tumors (Bian et al, 2020 ). Tumor necrosis factor receptor-associated factor 5 (TRAF5) is a cytoplasmic adapter that can trigger the NF-κB signaling pathway via its receptors and can take part in modulating nerve cell death, inflammatory reactions, and other neurological processes (Zhang et al, 2021 ). Zhang et al demonstrated that in PD, SNHG7 works as a ceRNA by sponging miR-425-5p and promoting TRAF5 (Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor receptor-associated factor 5 (TRAF5) is a cytoplasmic adapter that can trigger the NF-κB signaling pathway via its receptors and can take part in modulating nerve cell death, inflammatory reactions, and other neurological processes (Zhang et al, 2021 ). Zhang et al demonstrated that in PD, SNHG7 works as a ceRNA by sponging miR-425-5p and promoting TRAF5 (Zhang et al, 2021 ). In addition, SNHG10 is a lncRNA located on chromosome 14q32.13 and is involved in advancing several types of cancer (Sun Z. M. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…With HOTTIP sponging to miR-615-3p, HOTTIP downregulation alleviates microglial activation, pro-inflammatory cytokine secretion and neuron death by lowering the expression of FOXO1 [ 183 ]. By binding to the miR-425-5P/TRAF5 axis, SNHG7 serves as a ceRNA to modulate inflammation and oxidative stress in cell and mouse models [ 184 ].…”
Section: Microrna (Mirna)mentioning
confidence: 99%
“…Among the 17 newly studied lncRNAs, 13 were identified to aggravate oxidative stress and inflammatory responses in neurons, namely AL049437, HOTAIR, LINC00943, lncRNA-p21 (lnc-p21), MIAT, NEAT1, rhabdomyosarcoma 2-associate transcript (RMST), SNHG1, SNHG7, SOS1 intronic transcript 1 (SOS1-IT1), SRY-box transcription factor 2 overlapping transcript (SOX2-OT), taurine upregulated gene 1 (TUG1), and UCA1 (Cai et al, 2019 ; Ding et al, 2019 ; Zhai et al, 2020 ; Zhang L. et al, 2020 ; Zhao et al, 2020b ; Guo et al, 2021 ; Lian et al, 2021 ; Ma et al, 2021a ; Zhang et al, 2021 ; Zhou S. et al, 2021 ; Fan et al, 2022 ; Lang et al, 2022 ). The other four lncRNAs, namely JHDM1D antisense 1 (JHDM1D-AS1), myocardial infarction associated transcript 2 (Mirt2), small nucleolar RNA host gene 12 (SNHG12), and PART1, exhibited anti-oxidant and anti-inflammatory roles in models of PD, as evidenced by the decline in proinflammatory cytokines and increase in SOD contents (Han et al, 2019 ; Shen et al, 2021b ; Wang C. et al, 2021 ; Yan et al, 2021 ).…”
Section: Interaction Between Oxidative Stress and Regulatory Ncrnas I...mentioning
confidence: 99%